2021
DOI: 10.1002/mame.202100429
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Boron Nitride Based Hybrid Polymer Nanocomposites

Abstract: Boron nitride (BN) is an eminent inorganic compound having many interesting characteristics such as improved oxidation resistance, mechanical strength, good thermal conductivity (TC), higher bandgap, high chemical stability, thermal stability, high hydrophobicity, and electrical insulation. The use of BN as a filler in polymers is a well‐established strategy to tailor the properties of polymer composites. Recent studies depict an interesting urge to reap the synergistic effect of various nanofillers with BN in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 131 publications
0
18
0
Order By: Relevance
“…6,7 Many types of ceramics have been used to enhance the k of polymer-based composites. Hexagonal boron nitride (hBN) is one of the most common ceramic fillers used to increase k. [8][9][10] Hexagonal boron nitride has a large amount of anisotropic k and the k in the in-plane direction (a-axis, [100]) has reached values as high as 600 W/(m K). On the other hand, the k of hBN in the out-of-plane direction (c-axis, [002]) has shown about 30 W/(m K).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Many types of ceramics have been used to enhance the k of polymer-based composites. Hexagonal boron nitride (hBN) is one of the most common ceramic fillers used to increase k. [8][9][10] Hexagonal boron nitride has a large amount of anisotropic k and the k in the in-plane direction (a-axis, [100]) has reached values as high as 600 W/(m K). On the other hand, the k of hBN in the out-of-plane direction (c-axis, [002]) has shown about 30 W/(m K).…”
Section: Introductionmentioning
confidence: 99%
“…Good mechanical properties and chemical stability is expected from HDPE, which results in its applications in many industrial and daily life applications 11 . Hexagonal boron nitride (h‐BN) is a ceramic material with a density of 2.1–2.3 g/cm 3 , 12 an in‐plane thermal conductivity of about 600 W/mK, 13 and a structure much like graphite 14 . Due to the high breakdown voltage, high thermal conductivity, and electrical insulation, the incorporation of BN in polymer matrices has been the subject of increased interest in the recent years 7 .…”
Section: Introductionmentioning
confidence: 99%
“…They found that the addition of BN increases the ultimate tensile strength and Young's modulus 17 . A comprehensive overview of the BN‐based polymer nanocomposites, including HDPE‐BN, can be found in the following review papers 7,14,18–20 . On the other hand, some authors studied the effect of the arrangement of the fillers on the thermal conductivity of the PMCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations